2021
DOI: 10.1158/1078-0432.ccr-20-2278
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming MET-Dependent Resistance to Selective RET Inhibition in Patients with RET Fusion–Positive Lung Cancer by Combining Selpercatinib with Crizotinib

Abstract: and Company. L.M.S. reports consulting fees from EMD Serono, scientific advisory board roles for Loxo Oncology and Foghorn Therapeutics, and honorarium from Astra Zeneca. B.S.T. reports honoraria and research funding from Genentech and discovery board activities for Boehringer Ingelheim and Loxo Oncology; all stated activities were outside of the work described herein. M. Ladanyi reports ad hoc advisory board roles for

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 26 publications
0
76
0
Order By: Relevance
“… 29 Another four cases of acquired selpercatinib resistance with MET amplification were reported and, it was demonstrated that this could be overcome by combining selpercatinib with crizotinib. 30 Given that >1000 patients with RET alterations were enrolled on selective RET inhibitor trials globally, these trials are still in progress, and the resistance mechanisms have been reported in just a few patients so far, the frequencies of various resistance mechanisms remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Another four cases of acquired selpercatinib resistance with MET amplification were reported and, it was demonstrated that this could be overcome by combining selpercatinib with crizotinib. 30 Given that >1000 patients with RET alterations were enrolled on selective RET inhibitor trials globally, these trials are still in progress, and the resistance mechanisms have been reported in just a few patients so far, the frequencies of various resistance mechanisms remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ALK TKIs consists of both on-target and off-target mechanisms. Off-target resistance mechanisms to 4G ALK TKIs will likely involve MET amplification which has been reported with the use of next-generation ALK or RET TKIs [42] , [43] , [44] , [45] , [46] . On-target resistance mechanisms such as single, double, or triple mutations are likely to be the most logical mechanism of resistance and will largely depend on the structures of TPX-0131 and NVL-655.…”
Section: Potential On-target Resistance To 4g Alk Tkismentioning
confidence: 99%
“…For patients in which mutations in the RET kinase domain responsible for drug resistance were not detected, evidence exist mostly for the activation of bypass signaling pathways. MET dependence has been reported as a recurring and potentially targetable mechanism of resistance to selpercatinib and pralsetinib [81][82][83]. Preclinical studies have demonstrated that EGFR transduced bypass signals to critical downstream pathways which regulate cell proliferation and survival via ERK and AKT, enabling cancer cells to evade RET inhibitors.…”
Section: Reported Mechanisms Of Off-target Drug Resistancementioning
confidence: 99%